Bioprosthetic tricuspid valve thrombosis: Percutaneous PFO closure to improve hypoxia and respiratory failure. Issue 5 (25th October 2017) - Flueckiger, Peter; Singleton, Matthew; Vasu, Sujethra; Zhao, David
Abstract: Prosthetic valve thrombosis (PVT) is an increasingly recognized complication of bioprosthetic valve replacement, often resulting in abnormal hemodynamic, endothelial, and hemostatic conditions. Bioprosthetic PVT may lead to significant hemodynamic and clinical effects. In hemodynamically stable patients, first‐line treatment for bioprosthetic PVT is systemic anticoagulation. However, concomitant cardiovascular pathology may lead to additional clinical sequalae that requires acute therapeutic interventions. We describe two cases in which bioprosthetic PVT leads to hemodynamically significant intracardiac shunting through pre‐existing patent foramen ovales requiring percutaneous closure with a Cribriform AMPLATZER occluder device. We also review the treatment for bioprosthetic PVT and discuss important clinical and hemodynamic considerations.